Sleep medicine in Saudi Arabia: Current problems and future challenges - BaHammam Ahmed (Annals of Thoracic Medicine, 2011)
Sleep medicine is a relatively new specialty in the medical community. The practice of sleep medicine in Saudi Arabia (KSA) began in the mid to late nineties. Since its inception, the specialty has grown, and the number of specialists has increased. Nevertheless, sleep medicine is still underdeveloped in the KSA, particularly in the areas of clinical service, education, training and research. Based on available data, it appears that sleep disorders are prevalent among Saudis, and the demand for sleep medicine service is expected to rise significantly in the near future. A number of obstacles have been defined that hinder the progress of the specialty, including a lack of trained technicians, specialists and funding. Awareness about sleep disorders and their serious consequences is low among health care workers, health care authorities, insurance companies and the general public. A major challenge for the future is penetrating the educational system at all levels to demonstrate the high prevalence and serious consequences of sleep disorders. To attain adequate numbers of staff and facilities, the education and training of health care professionals at the level of sleep medicine specialists and sleep technologists is another important challenge that faces the specialty. This review discusses the current position of sleep medicine as a specialty in the KSA and the expected challenges of the future. In addition, it will guide clinicians interested in setting up new sleep medicine services in the KSA or other developing countries through the potential obstacles that may face them in this endeavor.